2013
DOI: 10.1073/pnas.1312033110
|View full text |Cite
|
Sign up to set email alerts
|

The deoxynucleotide triphosphohydrolase SAMHD1 is a major regulator of DNA precursor pools in mammalian cells

Abstract: Sterile alpha motif and HD-domain containing protein 1 (SAMHD1) is a triphosphohydrolase converting deoxynucleoside triphosphates (dNTPs) to deoxynucleosides. The enzyme was recently identified as a component of the human innate immune system that restricts HIV-1 infection by removing dNTPs required for viral DNA synthesis. SAMHD1 has deep evolutionary roots and is ubiquitous in human organs. Here we identify a general function of SAMHD1 in the regulation of dNTP pools in cultured human cells. The protein was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
285
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 218 publications
(310 citation statements)
references
References 45 publications
20
285
3
2
Order By: Relevance
“…As expected, cyclin E was present at the G1/S border and decreased as cells advanced into S phase, cyclin A2 accumulated during S and into G2, while cyclin B increased in G2/mitosis. SAMHD1 was present in all the phases and actually increased in confluent G1- and serum-starved G0 cells (Figure 2(a)), consistent with previous results[10]. In G1 and G0 T592 was not phosphorylated.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…As expected, cyclin E was present at the G1/S border and decreased as cells advanced into S phase, cyclin A2 accumulated during S and into G2, while cyclin B increased in G2/mitosis. SAMHD1 was present in all the phases and actually increased in confluent G1- and serum-starved G0 cells (Figure 2(a)), consistent with previous results[10]. In G1 and G0 T592 was not phosphorylated.…”
Section: Resultssupporting
confidence: 91%
“…Considering the low level of mRNA after 8 h from tetracycline removal, we calculated for the protein a half-life of at least 16 h. We assessed the phosphorylation of GFP-SAMHD1 using the antibody specific for pT592 and found that the phosphorylated form decreased similarly to the non-phosphorylated one (Figure 5(c)). In line with our previous data with SAMHD1-silenced fibroblasts where the protein declined slowly in the absence of SAMHD1 mRNA [10], these results suggest that in proliferating cells SAMHD1 is a stable protein and phosphorylation does not fast SAMHD1 turn-over.
10.1080/15384101.2018.1480216-F0005Figure 5.Turn-over of SAMDH1 in proliferating U2OS cells. A .
…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations